EFFECT OF ORGANIC WASTES AND NPK LEVELS ON THE NUTRIENT UPTAKE AND YIELD OF GROUNDNUT IN COASTAL SANDY SOIL - ELAYARAJA, D.; SINGARAVEL, R. (Annals of Agricultural Research, 2014)
An experiment was conducted at a farmers' field in sandy soil to study the effect of organics and NPK levels on the nutrient uptake and yield of groundnut. The soil (0-15 cm) had the following characteristics viz., organic carbon- 0.37%, pH - 8.54, EC- 1.51 dS m-1, available alkaline KMnO4-N 114.28 kg ha-1, Olsen P- 7.21 kg ha-1 and NH4OAC-K 124.74 kg ha-1. Four levels of NPK viz., no NPK, NPK (100%), NPK (125%) and NPK (150%) were used as treatments in main plots. Different sources of organics viz., control, composted coir pith (CCP) @ 12.5 t ha-1 and pressrnud (PM) @ 12.5 t ha-1 were used as treatments in subplots. The treatments were replicated thrice in a Factorial Randomized Block Design (FRBD). The test crop was groundnut var. VRI 2. The experimental results indicated that 150% NPK level among the inorganics and composted coirpith @ 12.5 t ha-1 was significantly superior in increasing the uptake of nutrients by groundnut. This treatment combination also proved most efficient in increasing the yield of groundnut by recording 2196 and 2930 kg ha-1 of pod and haulm yield.